ChemInform Abstract: Mechanically Induced Multicolor Change of Luminescent Materials. Issue 30 (July 2015) - Ma, Zhiyong; Wang, Zhijian; Teng, Mingjun; Xu, Zejun; Jia, Xinru
Abstract Review: 108 refs.